2019
DOI: 10.3314/mmj.19.007
|View full text |Cite
|
Sign up to set email alerts
|

2016 Epidemiological Survey of Dermatomycoses in Japan

Abstract: We report here the results of the 2016 epidemiological survey of dermatomycosis in Japan. In total, 6,776 cases were analyzed as follows: dermatophytosis, 5,772 cases (85.2%); candidiasis, 757 cases (11.2%); Malassezia infection, 235 cases (3.5%); and other fungal infections, 11 cases (0.2%). In dermatophytosis, tinea pedis was the most frequent (3,314 cases: ). Although the number of cases varied depending on the role of each cooperating medical institution in the area and on population composition, no signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
29
1
8

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(43 citation statements)
references
References 6 publications
5
29
1
8
Order By: Relevance
“…In addition, the most common age group affected by P. aeruginosa interdigital infections was the 60-69 years group. This corresponds with the age of onset of tinea pedis [17]. Furthermore, other predisposing factors, such as scratching or rubbing, unreasonable treatment, and hot-water scalding are more common in this age group (data not shown).…”
Section: Discussionmentioning
confidence: 68%
“…In addition, the most common age group affected by P. aeruginosa interdigital infections was the 60-69 years group. This corresponds with the age of onset of tinea pedis [17]. Furthermore, other predisposing factors, such as scratching or rubbing, unreasonable treatment, and hot-water scalding are more common in this age group (data not shown).…”
Section: Discussionmentioning
confidence: 68%
“…In terms of age, the present study examined a wider range of patients compared with previously reported surveys [15]. Due to aging of the Japanese population, the proportion of patients aged > 80 years is increasing, which could pose problems in the future [17][18][19]. Therefore, we conducted a more-detailed age-speci c evaluation than previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Onychomycosis caused by dermatophytes is found more frequently in the elderly than in younger patients. Patients in their 70s are the largest age population in Japan, accounting for 25.7% (420/1634) of cases according to a Japanese survey 7 . Age is the principal non‐modifiable risk factor for the development of onychomycosis.…”
Section: Discussionmentioning
confidence: 99%